Randomized controlled trial on improving pesticide label interpretation among farmers in Akkar Governorate, Lebanon: The impact of a whatsapp-delivered educational video - Nisreen Hassan Akkouch; Jalal Halwani; Issam Shaarani; Fouad Ziadeh (PLoS ONE, 2025)
Background Pesticide misuse poses significant health and environmental risks, particularly in low- and middle-income countries. In Lebanon, improper pesticide handling and a lack of understanding of pesticide labels among farmers are major concerns. This study evaluated the effectiveness of a WhatsApp-delivered educational video compared to traditional in-person educational sessions in improving farmers’ pesticide safety knowledge, label interpretation, and handling practices. Design This study employed a parallel-group, three-arm randomized controlled trial (RCT) with three groups: a traditional educational session group, a WhatsApp-delivered educational video group, and a control group receiving no intervention. Setting/participants The study was conducted in the coastal villages of Akkar Governorate, northern Lebanon, from June to August 2024. One hundred thirty- three agricultural farmers were recruited through systematic sampling from a list of registered farmers, based on their pesticide use and access to WhatsApp. Interventions Participants were randomly assigned to one of three groups: the control group received no intervention; the traditional education group participated in an in-person training session focused on pesticide safety, health risks, and label interpretation; the digital video group received a 4-minute educational video via WhatsApp, covering the same topics as the traditional session. Main outcome measures Primary outcomes included the ability to interpret Food and Agriculture Organization of the United Nations (FAO) pictograms, knowledge of pesticide health risks, and understanding the environmental impacts of pesticide misuse. Secondary outcomes assessed the use of personal protective equipment (PPE) and changes in pesticide handling practices. Results The video-based group showed the most significant improvement in pesticide handling, knowledge, and awareness of health and environmental risks, outperforming the traditional education group. The control group showed minimal changes. The video-based intervention was especially effective in enhancing the interpretation of pesticide labels, including complex pictograms and color codes. Conclusion The results demonstrate that WhatsApp-delivered video interventions are superior in improving pesticide safety knowledge and practices compared to traditional methods. This cost-effective, scalable approach provides a viable solution for disseminating agricultural safety education, particularly in resource-limited areas. The study highlights the potential of digital learning tools to reach a wide audience with fewer resources, contributing to safer pesticide use and reducing health and environmental risks. Trial registration International Standard Randomised Controlled Trial Number ISRCTN12809193